No shelf required : e-books in libraries - Polanka, Sue (American Library Association, 2011)
Sue Polanka brings together a variety of professionals to share their expertise about e-books with librarians and publishers. Providing forward-thinking ideas while remaining grounded in practical information that can be implemented in all kinds of libraries, the topics explored include an introduction to e-books and their different types, an overview of their history and development, e-book technology, why e-books are good for learning, and how librarians can market them to a wide range of users.--[back cover]